Video head impulse in comparison to caloric testing in unilateral vestibular schwannoma. (1st November 2016) - Tranter-Entwistle, Isaac; Dawes, Patrick; Darlington, Cynthia L.; Smith, Paul F.; Cutfield, Nicholas
Abstract: Conclusions: Although there was a statistically significant relationship between the results of the vHIT and the caloric test, the limited strength of this relationship suggests that, for unilateral vestibular schwannoma (UVS), caloric testing and vHIT may provide complementary information on vestibular function. Objective: There is limited information that can be used to determine which of the video head impulse test (vHIT) and caloric test might be better used in the diagnosis and management of UVS. In this study, a group of participants with un-operated UVS was studied using both methods. Methods: The subjects' vestibular function was assessed using the vHIT and caloric testing. Tumour size was quantified using MRI and their balance disturbance assessed using the Jacobsen Dizziness Handicap Inventory (DHI). Results: Twenty of 30 subjects had an abnormal canal paresis according to the Jongkees' criterion (> 0.25); however, only 10/30 had an ipsilesional vHIT gain of <0.79. Canal paresis could be predicted from the ipsilesional and contralesional vHIT gains. Tumour size could also be predicted from the ipsilesional vHIT gain and canal paresis. However, DHI scores could not be predicted from the degree of canal paresis, vHIT gain, or the MRI measures.